Thermoinhibition in parsley seeds (Bioscience Journal, 2017)
Temperature can exert great influence on germination, being considered optimal the temperature in which seed expresses its maximum germination potential in the shortest period of time. The germination of parsley seeds is slow, irregular and uneven. The aim of this study was to determine whether there is occurrence of thermodormancy or thermoinhibition of parsley seeds as a function of temperature variations. The experimental design of the first stage was completely randomized (CRD) consisting of 7 temperatures and 4 replicates and the second stage in a 3x3 factorial scheme consisting of 3 parsley cultivars and 3 germination temperatures with 4 replicates. Seeds of the different cultivars did not germinate at temperature of 35°C. Parsley seeds showed thermoinhibition at high temperatures, being necessary to elucidate the mechanisms involved in this process.